2020
DOI: 10.1080/02678292.2020.1786177
|View full text |Cite
|
Sign up to set email alerts
|

Tunability of the elastocaloric response in main-chain liquid crystalline elastomers

Abstract: Materials exhibiting a large caloric effect could lead to the development of new generation of heat-management technologies that will have better energy efficiency and be potentially more environmentally friendly. The focus of caloric materials investigations has shifted recently from solid-state materials toward soft materials, such as liquid crystals and liquid crystalline elastomers. It has been shown recently that a large electrocaloric effect exceeding 7 K can be observed in smectic liquid crystals. Here,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The liquid crystal-containing elastomers studied in this work undergo a mechanotropic phase transition, from disordered to nematic, which is asssociated with an elastocaloric temperature change of up to ∆T + = 2.9 K. This represents a large improvement over existing reports on the elastocaloric response in other liquid crystalline polymer networks, which typically demonstrate ∆T + ∼ 1 K, 14,22 . Further, these initial results approach the magnitude of the temperature changes of 5.2 and 6.5 K reported for electrocaloric LC systems.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The liquid crystal-containing elastomers studied in this work undergo a mechanotropic phase transition, from disordered to nematic, which is asssociated with an elastocaloric temperature change of up to ∆T + = 2.9 K. This represents a large improvement over existing reports on the elastocaloric response in other liquid crystalline polymer networks, which typically demonstrate ∆T + ∼ 1 K, 14,22 . Further, these initial results approach the magnitude of the temperature changes of 5.2 and 6.5 K reported for electrocaloric LC systems.…”
Section: Discussionmentioning
confidence: 69%
“…Recent literature reports detail the elastocaloric response of LCEs. Experimental efforts have so far demonstrated elastocaloric temperature changes of only ∆T ∼ 1 K. 14,22 Lavrič et al observed ∆T = 1 K at a strain of ε = 90% and detailed that this ∆T was observed across a range of crosslink density. 22 Skačej has reported molecular simulations that suggest the elastocaloric effect in mainchain LCEs could yield a ∆T > 10 K. 23 However, the simulations underestimate the specific heat of liquid crystal-containing systems, which likely leads to an overestimate of the elastocaloric temperature change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, stimulus responsive polymers have become a hotspot in research of advanced functional materials. , One of the most competitive candidates refers to liquid crystalline polymer (LCP), in which the ordered liquid crystal mesogens are frozen by covalently cross-linked polymer network. Because of the combination of the programmable orientation of liquid crystal and the elasticity of polymer matrix, LCP has been proved as an outstanding matrix to prepare smart actuators and soft robots, presenting great potentials in multiple fields such as biomimetic actuators, artificial muscles, , functional sensors, , and so on. In order to broaden the practical applications of the LCP materials, various LCP devices with different stimulus responses were prepared, including light, electricity, , heat, , magnetism, force, and humidity. , …”
Section: Introductionmentioning
confidence: 99%
“…3−7 Because of the combination of the programmable orientation of liquid crystal and the elasticity of polymer matrix, LCP has been proved as an outstanding matrix to prepare smart actuators and soft robots, presenting great potentials in multiple fields such as biomimetic actuators, 8 artificial muscles, 9,10 functional sensors, 11,12 and so on. 13−15 In order to broaden the practical applications of the LCP materials, various LCP devices with different stimulus responses were prepared, including light, 16−19 electricity, 20,21 heat, 22,23 magnetism, 24 force, 25 and humidity. 26,27 Compared with other stimuli, humidity is a nontoxic, harmless trigger that can be easily obtained.…”
Section: Introductionmentioning
confidence: 99%